Den farlige biografi. Om Lis Jacobsens arkiv og den historiske biografis udfordringer - Possing, Birgitte (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
The article describes an unusually large private archive kept in the Royal Library’s Department of Manuscripts. It is precisely registered, accessible and contains letters, pocket diaries and notebooks, manuscripts and files, treatises and records, accounts, songs and newspaper clippings. It leaves the impression of someone who was aware of her worth and had the resources to the have the traces of her life’s work ordered and preserved. The scheme reflects the archive creator’s self-image. It consists of 193 boxes, which corresponds to 20 shelf meters. What is unusual is that the archive was left by a woman, namely Lis Jacobsen (1882–1961), who was one of Denmark’s few great female scientific personalities in the 20th century. She was a fundraiser, editor, researcher, organizer and founder of The Danish Society for Language and Literature. The article ascertains her historical importance, describes the research possibilities inherent in the archive, and argues that an historical biography of her life and work would be justified. The author accordingly welcomes Kristian Hvidt’s biography Researcher. Furie. Front Soldier (2011), but is puzzled by the reviewers’ reception of it. Proceeding both from the critical reviews and from LJ’s archive and historical importance, the author analyses the historical biography in question. Her aim is to understand why the reception of the biography was so critical. She reviews some of the methodological and analytical stipulations made on a modern biography and argues that the present biographer has ignored several of these. The article is thus an essay that combines an objectively critical review with an account of a valuable cultural treasure at The Royal Library, and also an introduction to modern biographical method. Other recent biographical works are referred to as counter-examples of the LJ-biography under review.